URIC ACID IN TYPE 2 DIABETES MELLITUS - DR.S.V.MYTHILI; A.JAMUNA RANI (International Journal of Pharma and Bio Sciences, 2013)
Whether Uric acid is an antioxidant or pro oxidant has been a topic of debate since long. The antioxidant activity of uric acid has been proved by various studies. This study was carried out among a group of Type 2 Diabetic patients attending Sree Balaji Medical College and Hospital. The FPG, PPPG levels were assayed along with Uric acid levels. We found a minimal decrease in serum uric acid levels among the diabetic patients in comparison with Healthy controls. The results support the idea that uric acid is an antioxidant which is being used up in combating the oxidative stress.